2023
DOI: 10.1002/adma.202212267
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis Induced by ROS Responsive Nanoparticles with Elesclomol and Copper Combined with αPD‐L1 for Enhanced Cancer Immunotherapy

Abstract: their quality of life. [1] Despite local therapy, approximately one-third of patients will relapse and develop metastatic diseases. [2] In recent years, immunotherapy has made great progress. Anti-programmed cell death protein ligand-1 antibody (αPD-L1) has been approved by the US Food and Drug Administration for bladder cancer treatment since 2016, the usage of which spanning from non-muscle-invasive to metastatic disease. [3] However, many bladder cancer patients fail to respond to these treatments. [4] On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(57 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…Accumulation of large amounts of Cu + in cancer cells can disrupt specific mitochondrial metabolic enzymes, in particular DLAT, a subunit of the pyruvate dehydrogenase complex found in mitochondria, which mainly regulates the tricarboxylic acid cycle. Cu + binding to DLAT promotes DLAT oligomerization and increases insoluble DLAT accumulation, which further leads to proteotoxic stress and cell death. Hence, DLAT oligomerization was further evaluated by immunofluorescence imaging. As shown in Figure j, compared with the control group, Cu-DBCO- or Cu-DBCO/C-treated 4T1 cells exhibited obvious DLAT aggregation, indicating that Cu-DBCO can promote the aggregation of lipidated proteins and ultimately induce cell death by cuproptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulation of large amounts of Cu + in cancer cells can disrupt specific mitochondrial metabolic enzymes, in particular DLAT, a subunit of the pyruvate dehydrogenase complex found in mitochondria, which mainly regulates the tricarboxylic acid cycle. Cu + binding to DLAT promotes DLAT oligomerization and increases insoluble DLAT accumulation, which further leads to proteotoxic stress and cell death. Hence, DLAT oligomerization was further evaluated by immunofluorescence imaging. As shown in Figure j, compared with the control group, Cu-DBCO- or Cu-DBCO/C-treated 4T1 cells exhibited obvious DLAT aggregation, indicating that Cu-DBCO can promote the aggregation of lipidated proteins and ultimately induce cell death by cuproptosis.…”
Section: Resultsmentioning
confidence: 99%
“…94–96 In this study, an additional combination of immune checkpoint blocking (ICB) treatment, e.g. administration of PD-1 or PD-L1 antibodies, 97–99 may be able to further enhance the anti-tumor effects, which may deserve more investigations in the future. Tumors harvested from mice treated with HMPR displayed the smallest size (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since first reported in 2022, this copper-dependent cuproptosis has sparked tremendous attention in cancer therapy and a few studies of cuproptosis-based cancer therapy have recently been reported. ,, However, the application of cuproptosis in tumor treatment suffers from several challenges: (a) the intracellular copper level was too low to realize therapeutic activity, (b) nonselectivity and potential systemic toxicity of copper ions resulted in off-target toxicities and unpredictable side effects, , and (c) there is difficulty in transporting free copper ions into cancer cells because excess copper ions were discharged out of the cells through copper exporters like ATP7A and ATP7B . Given the circumstances, increasing the copper level in cancer cells by selective delivery of exogenous copper ions was expected to promote cuproptosis and avoid potential toxicities to healthy tissues/organs. ,, Additionally, in comparison to Cu 2+ , Cu + was found to be preferable for cuproptosis because Cu + could directly bind to lipoylated TCA cycle proteins . Hence, how to deliver copper ions in the form of Cu + to cancer cells is also a concern in the development of effective cuproptosis therapy.…”
Section: Introductionmentioning
confidence: 99%